Al-Asrâr fî Tikrâr Hiwâr al-Nabi Musa wa al-‘Abd fî Sûrah al-Kahfi: Tahlîl al-Îjâz wa al-Ithnâb - Latif, Abdul; Amrulloh, Muhammad Afif; Mahliatussikah, Hanik; Muflihah, Intan; Wahidah, Yeni Lailatul (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
The problem in this study it is the reason why Prophet Khidr repeated his words -You will not patient with me -  to the prophet Moses, even though the prophet Moses was known as the intelligent prophet. This research uses the theory of ijaz and ithnab (brevity and redundancy) in the science of rhetoric. This theory finds abbreviated word types and extended word types. This research uses a qualitative approach that is descriptive through a literature review. Researcher found there are sixteen ijaz sentences including sentences by removing related sentences, five sentences by removing adjectives, one sentence by removing letters, one sentence by removing dispersed words, one sentence by removing the divine predicate, one sentence miracle of delivering sentences. The four ithnab sentences that the researcher found are as follows. First, the expressive sentences by mentioning special sentences after mentioning general sentences that serve to emphasize specific sentences. Secondly, the redundancy sentence is the appendix by bringing up the second sentence which is similar to the first sentence that intends to emphasize the idea of the sentence. Third, verbosity sentences that use the inclusion allowance that serve to explain the previous sentence and which are not yet clear. Fourth, verbosity and repetition sentences that work to persuade the other person to accept the advice. The reason why ‘Abd’ repeated his words to the prophet Moses was not because Moses was stupid, but because of Prophet Moses' spirit in seeking knowledge and allowing him to continue searching for guidance with the ‘Abd’.Keywords: Advice, Repetition, Spirit.